Influence of intra row spacing on weed suppression in cucumber (Cucumis sativus) production in humid rainforest agro-ecological zone of lagos, Nigeria - Sanni KO; Adenubi OO (Global Journal of Ecology - Peertechz Publications, 2020)
The use of intra row spacing in crops production has been advocated as a technological alternative to obtain optimum yield increases, due to the better use of resources. The experiment was carried out at the Teaching and Research Farm, Lagos State Polytechnic, Ikorodu in Randomized Complete Block Design with three treatments (1m×0.9m, 1m×0.6m and 1m×0.3m) and replicated three times. Data were collected on weed fresh weight, weed cover score, vine length, and number of leaves at 3, 6 and 9 Weeks After Planting (WAP); number of fruits, fruit length, fruit diameter to evaluate weed suppression, cucumber growth and yield performance. The data were subjected to Analysis of Variance (ANOVA) and significant treatment means were separated using Duncan Multiple Range Test (DMRT) at 5% probability level. Results from the study showed that cucumber planted at 1m x 0.3m spacing had the highest fruit yield (96.33kg/ha) followed by 1m x 0.6m (71.11kg/ha) and 1m×0.9m recorded the least (37.4ikg/ha). While, weed infestation was significantly (p<0.05) suppressed at 1m x 0.6m spacing (6.33) followed by 1m x 0.3m (96.67). Based on the results obtained from the study, it is recommended that 1m×0.6m and 1m×0,3m spacing could be adopted by farmers in the study area for cultivation of cucumber as this give the best yield and suppress weed infestation. Further study is also recommended in other agro ecological zones in the rainforest of south western Nigeria in order to explore the possibility of having uniform planting spacing for cucumber.